Placental Implantation Abnormalities and Risk of Preterm Delivery: A Systematic Review and Meta-Analysis. Issue 4 (December 2016) - Vahanian, S.A.; Lavery, J.A.; Ananth, C.V.; Vintzileos, A.
Abstract : ( Am J Obstet Gynecol 2015;213(suppl):S78–S90) A rise in placental implantation abnormalities (PIAs) such as placenta previa, placenta accreta, vasa previa, and velamentous cord insertion have led to an increase in cesarean delivery rates in the past 2 decades. PIAs account for 5.6% to 8.7% of indicated preterm deliveries at <35 weeks' gestation. This study presented a metaanalysis of PIAs in relation to preterm delivery and other adverse perinatal outcomes.